2020
DOI: 10.1177/1120672120974296
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep disturbance with diabetic retinopathy

Abstract: Purpose: Diabetes mellitus (DM) patients are more likely to experience sleep disturbances than normal. Sleep disturbances may contribute to the development of diabetic retinopathy (DR) by higher inflammatory markers in circulation. We investigated the association between sleep quality and DR. Methods: Institutional case control study with type 2 DM patients of <10 years duration and HbA1c ⩽8%; 70 cases with DR and 70 controls without DR (NODR) (power 0.8). Sleep quality was assessed by Pittsburg sleep quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…A total of three ( 7 , 12 , 13 ) articles reported that the PSQI score for sleep quality revealed its relationship with DR risk. There was no homogeneity among the studies (P = 0.50, I 2 = 0%), so the fixed effect model was used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of three ( 7 , 12 , 13 ) articles reported that the PSQI score for sleep quality revealed its relationship with DR risk. There was no homogeneity among the studies (P = 0.50, I 2 = 0%), so the fixed effect model was used.…”
Section: Resultsmentioning
confidence: 99%
“…Sleep disturbances have been found to be associated with abnormal glucose metabolism and an increased risk of diabetes ( 6 ). Sleep disturbances may be due to decreased sleep duration and/or decreased sleep quality ( 7 ). At present, the amount of clinical literature on the relationship of sleep quality and duration with DR is increasing year by year.…”
mentioning
confidence: 99%
“…First, with our country being the diabetes capital of the world, there is no study reporting the screening of OSA in DR patients in India. Though a recent study from India reported a positive association between sleep disturbance and DR,[ 30 ] it did not screen for OSA in DR. However, second, while the majority of the studies have shown the prevalence of OSA in a population of DM, and not DR, its prevalence in DR population remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cross-sectional studies have shown that short or long sleep duration is associated with DR ( 7 , 8 ). Another study elucidated the positive correlation of sleep quality with DR severity as well as increased sleep latency in patients with DR ( 9 ). Among elderly subjects with diabetes, DR was more prevalent in the poor sleep quality group ( 10 ).…”
Section: Introductionmentioning
confidence: 99%